Fundraising dalam Lembaga Filantropi Islam - Usfiyatul Marfu'ah; Muhammad Aji Shadiqin (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2022)
Surviving during a pandemic is not easy, including for philanthropic institutions. The Amil Zakat Institution is one of the Islamic philanthropic institutions that collect funds from muslims. Fundraising (collecting funds) in this pandemic period has two interrelated sides. The firdt side is not easy, because everyone is affected economically from the pandemic. On the other side, fundraising is important, to be able to help people who are most severely affected. This study discusses the methode used by philanthropic institutions in raising funds during the pandemic, through two research questions. First, what is the fundraising procedure during a pandemic. Second, how to increase the number of donors during a pandemic. Through descriptive qualitative methode, this reseaarch explore data by means of observation, interviews, and documentation. The result of the study show that first, the fundraising conducted by zakat management institutions is not much different before the pandemic, it’s just that the limitation of working time and meeting other people during the pandemic creates obstacles. Thus, efforts are being made to strengthen fundraising through online. Second, increasing the number of donors during a pandemic is not an easy endeavor. Therefore, the increase in the number of donors is carried out qualitatively, by taking care of existing donors through the best service. Thus, the implications of this study indicate that the pandemic is a formidable challenge for philanthropic institutions to be able to survive abd provide maximum service to the community.